Illicit drug use derived from wastewater-based epidemiology in Iran, their removal during wastewater treatment, and occurrence in receiving waters - Anvar Asadi; Shabnam Zarei; Nebile Daglioglu; Evsen Yavuz Guzel; Neda Ravankhah (Heliyon)
This study aimed to measure the licit and illicit drug concentrations in wastewater treatment plants (WWTPs), their removal efficiency, and their consumption rate by wastewater-based epidemiology (WBE) approach. A 2-season monitoring program was undertaken for the first time in Iran. Residues of licit and illicit drugs (amphetamine, 3,4-methylenedioxyamphetamine, methamphetamine, codeine, 3,4-methylenedioxymethamphetamine, heroin, cocaine, and methadone) and major metabolites (benzoylecgonine, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine and 6-monoacetylmorphine) were analyzed by LC-MS/MS in composite sampling after solid phase extraction method. These analytes were also measured in rivers vicinity to selected cities. The detected concentration in raw wastewater was converted into the quantity of illicit drugs per capita using back-calculation. There was no detection of cocaine, its metabolite benzoylecgonine, or 3,4-methylenedioxymethamphetamine in any of the samples. Among the analytes measured, morphine and codeine exhibited the most prevalent occurrence and highest concentration levels in all the samples. Heroin was the main illicit drugs used in the studied population with a mean consumption rate of 6108 and 158 mg/day/1000 inh. in cold and warm seasons, respectively. The removal efficiencies of drugs during wastewater treatment ranged from 3.5 % (3,4-methylenedioxyamphetamine) to >99 % (amphetamine, methamphetamine, and codeine); however, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine demonstrated a negative removal within WWTPs. This study provides crucial insights into the consumption of illicit drugs in Iran, as well as the release of illicit drugs and their metabolites through WWTPs.